Immunosorbent assay using gold colloid cluster technology for determination of IgEs in patients’ sera - Haifa Al-Dubai (Dove Medical Press, 2010)
Haifa Al-Dubai1, Irene Lichtscheidl2, Martina Strobl1, Gisela Pittner1, Fritz Pittner11Department of Biochemistry, Max F Perutz Laboratories, University of Vienna, Vienna, Austria; 2Institute of Cell Imaging and Ultrastructure Research, Vienna, AustriaAbstract: This study focuses on the development of a sensitive and simple cluster-linked immunosorbent assay (CLISA) using gold colloidal cluster labeling for determination of proteins such as antigens (Ags) or antibodies (Abs). Abs for detection can be labeled with gold colloid clusters (GCCs). The Fc domain of the Abs binds to the clusters, and the Fab domain to the Ag on a nitrocellulose membrane or a microtiter plate as a support for dot-blotting. The signal of positive interaction between GCC-labeled Abs and its dotted Ag is detectable by the naked eye and can be quantified by comparison to a color scale prepared from a dilution series of known sample concentrations. The colored reaction product is stable for prolonged periods and does not fade, making this method a simple, fast, and convenient means for detection of Ag or Ab biorecognitions and an alternative to enzyme-linked immunosorbent assay. Several interactions between different Ags or Abs (eg, ß-lactoglobulin) and solutions avoiding gold colloidal cluster flocculation (eg, using protein G) were studied. CLISA was tested for other analytical purposes such as detection of IgEs in patients’ sera.Keywords: ELISA, allergen, patient sera, CLISA, immunoassay, ß-lactoglobulin